2004
DOI: 10.1021/je049928n
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Study of Lysozyme in Dimethyl Sulfoxide + Water Solution at 298.15 K

Abstract: The viscosities, η, of ternary mixtures of water (1) + dimethyl sulfoxide (2) + lysozyme (3) were measured, and the intrinsic viscosities of lysozyme were determined by extrapolating the reduced viscosities to infinitely dilute lysozyme concentration at 298.15 K. A binary mixture of water + dimethyl sulfoxide had a maximum deviation of viscosity at approximately 0.33 mol fraction of dimethyl sulfoxide (x 2 ). Lysozyme unfolded and aggregated with an accompanying increase in the intrinsic viscosity of lysozyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
4
10
0
Order By: Relevance
“…The corresponding hydrodynamic diameter [24] is 4.1 nm which is similar to the molecular size calculated by the molecular modeling of the monomeric 1 (Figure 5 b). Dynamic light scattering (DLS) clearly showed the aggregation of 1 under the same condition.…”
supporting
confidence: 79%
“…The corresponding hydrodynamic diameter [24] is 4.1 nm which is similar to the molecular size calculated by the molecular modeling of the monomeric 1 (Figure 5 b). Dynamic light scattering (DLS) clearly showed the aggregation of 1 under the same condition.…”
supporting
confidence: 79%
“…Theoretical (Zhou, 1995) and experimental (Ahmad & Salahuddin, 1974;Lefebvre 1982;Areas et al, 1996;Monkos, 1997;Kamiyama et al, 2004;Pan et al, 2009) studies on the viscosity of various lysozyme solutions have been reported previously. According to a theoretical analysis (Zhou, 1995) the intrinsic viscosity is strongly influenced by the hydration level of the protein.…”
Section: Introductionmentioning
confidence: 95%
“…A high increase in the protein viscosity was also induced by other organic solvents like tetramethylurea (TMU) [29] and dimethylsulfoxide (DMSO) [29,30]. The pseudoplastic behavior of the protein in TMU indicated that the lysozyme existed in the elongated conformation and was able to reorient under shear stress.…”
Section: Resultsmentioning
confidence: 99%